Water Monitoring System using Automatic Shut-Off Valves - Ahmad Jamil, Muhammad Ikhwan Mirza; Mohamed Yusof, Anizam; Ab Rahman, Azmanirah (Research and Innovation in Technical and Vocational Education and Training, 2022)
Clean and safe water is supplied directly into the water storage tank of a house can provide comfort to the whole house. About 6 to 8 million people die each year due to water-related diseases. The existing water quality monitoring system with solenoid valves was only developed at the pre-water distribution stage and was designed only. Therefore, this study aims to design, develop and test the functionality of a water quality monitoring system with automatic shut-off valves and the notification message sender. This water quality monitoring system was developed using an engineering design process that consists of five phases: ask, imagine, plan, develop, and test. As a result of the product testing phase, this developed system has appropriately operated according to the program instructions in the NodeMCU ESP32 microcontroller. The water pH sensor and the total dissolved solids sensor can take readings of water quality values ​​well and be displayed on the Blynk app display on smartphones. The water pH sensor can detect the pH value around 7.00 to 7.01 for a buffer solution with a pH value of 7.01. While for the lemon extract solution, the water pH sensor can detect a value of 1.86. For the total dissolved solids sensor, this sensor can detect the total dissolved solids around 0 to 494 for tap water while increasing up to a value of 4470 after salt is added. Solenoid valves that are assigned to block the passage of water can also operate properly according to set standards. The water filter used can only reduce the number of dissolved solids. Overall, the water quality monitoring system developed can help consumers always receive quality and safe water. Suggestions for improving the developed system are also submitted to ensure more effective functionality.